2018
DOI: 10.1136/bmjsem-2018-000459
|View full text |Cite
|
Sign up to set email alerts
|

Changes in northern hemisphere male international rugby union players’ body mass and height between 1955 and 2015

Abstract: ObjectivesWe sought to establish the effects of professionalism, which officially began in 1995, on the body mass and height of northern hemisphere male international rugby union (RU) players. We hypothesised that mass would significantly increase following professionalism. We also investigated the changes in size of players according to their playing position, and we compared changes to rugby league (RL) players and the public.MethodsThe body mass and height of players representing their international team fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…This confirms previous research showing large increases soon after professionalism 4 followed by a levelling off in body mass, 4 5 but extends those previous findings to the most recent RWC in 2019, and explores the time-course of the increases at each RWC rather than over decades. 4 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This confirms previous research showing large increases soon after professionalism 4 followed by a levelling off in body mass, 4 5 but extends those previous findings to the most recent RWC in 2019, and explores the time-course of the increases at each RWC rather than over decades. 4 …”
Section: Discussionsupporting
confidence: 90%
“… 4 The result was an overall increase in average player mass of 24.3% (84.8 kg in 1955 to 105.4 kg in 2015), comprised of a relatively small increase between 1955 and 1995 (approximately 5%), and a much larger increase of almost 20% from 1995 to 2015. 4 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, research within soccer has demonstrated increases in the volume of high-intensity running distance alongside the frequency and successfulness of technical characteristics completed during the Premier League between 2006 and 2012 (Barnes et al, 2014;Bush et al, 2015). Within rugby, players' average body mass has increased from 84 to 105 kg between 1955 and 2015 (Hill et al, 2018) while rules and tactics have changed within boxing since 2013 (Davis et al, 2018). These examples demonstrate the numerous changes to the demands of sports, which may have occurred for multiple reasons (e.g., rule changes, advancements in coaching and sport science) but provide evidence that sports evolve over time.…”
Section: Part B: Understanding Sport and Predicting The Futurementioning
confidence: 99%
“…2018 handball), especially in some positions' players. For example, Hill et al [5] determined that international level rugby players' body mass has significantly increased since 1995: in 1955 the mean rugby players' body mass was 84.8 ± 8.2 kg but in 2015, it was 105.4 ± 12.1 kg, an increase of 24.3%. Between 1955 and 2015, the body mass of forwards increased steadily, whereas that of backs has mostly gone up since 1995.…”
Section: Introductionmentioning
confidence: 99%